ANALYSIS OF THE POEM (KHAZAL) ALISHER NAVOI'S PRAISE (On the example of “Garoyib us sigar”) - Karimova Nilufar Majidovna; Axadjon Muhammadiyev (Journals Park Publishing, 2022)
In this article we has analyzed Alisher Navoi's two-time praise Ghazal in the “Garoyib us sigar” and draws relevant scientific conclusions.
Keywords: Garoyib us-sigar, devon, praise, mysticism, romance, appearance, disclosure, mystery.